Qualitative analysis of career paths of women in the trades, 2001 to 2010 - Watson, I (My University, 2012)
This study tracks the fortunes of a group of women working in the trades occupations in 2001, following them through the labour market until 2010. It is a qualitative study, in so far as the findings reported here cannot be generalised to the Australian population. This report is a study of women who worked in trades occupations in 2001 and who continued to be surveyed through to 2010. The geographical coverage is Australia and the sample of women is a representative sample of women working in the trades in 2001. The data for this study come from HILDA, the Household, Income and Labour Dynamics in Australia Survey, which is the largest and most comprehensive data source currently available for studying changes in the Australian labour market over time. Despite the use of representative survey data, this study is a qualitative one. What does this mean? It means that the findings of this report, such as the patterns of labour mobility uncovered in this this study, cannot be generalised to the Australian population. The reason is simple: the number of women in the study is too small, and diminishes considerably over time. If these findings were to be generalised to a larger population the margin of error for these population estimates would be such that no meaningful conclusions could be drawn. Moreover, even though the study begins in 2001 with a representative sample of women, by the end of the period that representativeness has been lost because of women leaving the sample. Consequently, this study is qualitative in that no claims are made beyond the sample. As well as case study discussion, this report also contains numerous tables and diagrams. However, all of this quantitative material is still qualitative in scope, meaning that its conclusions refer only to this sample of women, not to the Australian population of women trades workers more generally. For this reason, no weighting has been applied to the data (which is usually done when one seeks to extrapolate beyond the sample and produce population estimates.) Among the issues looked at, two are particularly illuminating: earnings and job satisfaction. The former are presented as age earnings profiles, which essentially depict the average earnings of a group of workers at each age level. This provides a particularly useful insight into the lifecycle aspects of work. The various aspects of job satisfaction include satisfaction with pay, job security, the job itself, hours of work, and worklife balance. Together with the earnings, these measures throw light on the possible motives which might explain some of the labour market transitions which are mapped in this report. Do women leave their jobs in the trades because the pay is too low, or because the hours don’t suit them? These are the kinds of questions which these data items help answer. The conclusions reached in this report are impressionistic, not definitive. This is because the sample size is so small. Not only does this prevent one generalising the findings to a larger population—as noted above—but it also means that the any conclusions drawn here are tentative. A small change in the sample, for example, might see a different conclusion drawn.
Report for Office for Women's Policy
Keywords: Gender -- Female; Disadvantage -- Inequality; Employment -- Occupations and careers; Gender; Labour market; Gender; Disadvantage; Employment; Occupations and careers; Female; Inequality; Gender; Employment and unemployment